Large Scale Conversion of Trilobolide into the Payload of Mipsagargin: 8-O-(12-Aminododecanoyl)-8-O-Debutanoylthapsigargin - Zimmermann, Tomáš; Drašar, Pavel; Rimpelová, Silvie; Christensen, Søren Brøgger; Khripach, Vladimir A; Jurášek, Michal (Biomolecules, 2020)
In spite of the impressing cytotoxicity of thapsigargin (Tg), this compound cannot be used as a chemotherapeutic drug because of general toxicity, causing unacceptable side effects. Instead, a prodrug targeted towards tumors, mipsagargin, was brought into clinical trials. What substantially reduces the clinical potential is the limited access to Tg and its derivatives and cost-inefficient syntheses with unacceptably low yields. Laser trilobum, which contains a structurally related sesquiterpene lactone, trilobolide (Tb), is successfully cultivated. Here, we report scalable isolation of Tb from L. trilobum and a transformation of Tb to 8-O-(12-aminododecanoyl)-8-O-debutanoylthapsigargin in seven steps. The use of cultivated L. trilobum offers an unlimited source of the active principle in mipsagargin.
Keywords: butyráty; techniky syntetické chemie; Neoplasms; rostlinné extrakty; nádory; fytogenní protinádorové látky; Molecular Structure; Furans; lidé; Butyrates; thapsigargin; Chemistry Techniques, Synthetic; Carbon Dioxide; Fruit; furany; Antineoplastic Agents, Phytogenic; ovoce; superkritická fluidní chromatografie; molekulární struktura; sarkoplazmatická Ca2+-ATPáza; oxid uhličitý; Sarcoplasmic Reticulum Calcium-Transporting ATPases; Plant Extracts; Chromatography, Supercritical Fluid; Apiaceae; Thapsigargin; Humans